Features of teaching the discipline "Nanotechnologies in natural sciences" at the M. Kozybayev North Kazakhstan University - Useinov Б.М.; Markova А.Г.; Первиков, А.В.; Sartin С.А.; Shogzhanova М.Б.; Seilbekova Г.У. (Recent Contributions to Physics, 2024)
. Nanotechnology has captured the information field on an impressive scale, which is in one way or another related to scientific topics. In the modern world, the term "nanotechnology" is heard by almost every layman, for marketing purposes there are abuses with reference to this area. A definition is given that restricts the scope of this term. At the same time, breakthrough opportunities with the use of this interdisciplinary field for science, the latest outstanding research both for the promotion of digitalization and for the knowledge of man himself are shown. Since 2022, North Kazakhstan University has been conducting classes in the discipline "Nanotechnology in Natural Science Research" using high-precision modern equipment. The goal is to reveal the features of teaching this discipline at the Department of Physics. The importance of training specialists of various educational programs of the natural sciences in this discipline, the need to apply practical research skills on advanced scientific equipment: atomic force microscope, scanning tunneling microscope are considered. The results of scanning by students obtained in laboratory classes are given. The aspects of teaching this discipline at the North Kazakhstan University at the Department of Physics are revealed, the importance of the knowledge and skills gained in the formation of a future competitive specialist in the labor market is shown.